The Adaptation of the Wechsler Intelligence Scale for Children—5th Edition (WISC-V) for Indonesia: A Pilot Study - Whisnu Yudiana; Marc P. H. Hendriks; Christiany Suwartono; Shally Novita; Fitri Ariyanti Abidin; Roy P. C. Kessels (Journal of Intelligence)
The Wechsler Intelligence Scale for Children (WISC) is a widely used instrument for assessing cognitive abilities in children. While the latest fifth edition (WISC-V) has been adapted in various countries, Indonesia still relies on the outdated first edition, a practice that raises substantial concerns about the validity of diagnoses, outdated norms, and cultural bias. This study aimed to (1) adapt the WISC-V to the Indonesian linguistic and cultural context (WISC-V-ID), (2) evaluate its psychometric properties in a pilot study with an Indonesian sample, (3) reorder the item sequence of the subtests according to the empirical item difficulty observed in Indonesian children’s responses, and (4) evaluate the factor structure of the WISC-V-ID using confirmatory factor analysis. The adaptation study involved a systematic translation procedure, followed by psychometric evaluation with respect to gender, age groups, and ethnicity, using a sample of 221 Indonesian children aged 6 to 16 years. The WISC-V-ID demonstrated good internal consistency. Analysis of item difficulty revealed discrepancies in item ordering compared to the original WISC-V, suggesting a need for item reordering in future studies. In addition, the second-order five-factor model, based on confirmatory factor analysis, indicated that the data did not adequately fit the model, stressing the need for further investigation. Overall, the WISC-V-ID appears to be a reliable measure of intelligence for Indonesian children, though a comprehensive norming study is necessary for full validation.